Antithrombotic therapy in patients with atrial fibrillation and coronary artery disease - Abdelmoniem Moustafa (Thieme Medical and Scientific Publishers Pvt. Ltd., 2019)
Atrial fibrillation and coronary artery disease are commonly coexisting conditions that necessitate the use of an oral anticoagulant as well as dual antiplatelet therapy. Commonly referred to as triple oral antithrombotic therapy (TT), this helps prevent ischemic stroke and myocardial infarction but comes at the expense of an increased risk of bleeding. There is a growing body of evidence that the omission of aspirin from TT has the same preventive efficacy in terms of major adverse cardiacvascular and cerebrovascular events (MACCE) with significantly lower bleeding events. The combination of antiplatelet agents and direct oral anticoagulants (DOAC) is a matter of ongoing research. However, initial studies showed favorable safety profile of DOAC over vitamin K antagonist in combination with antiplatelet agents.